Research on Data Mining Method of TCM Prescription Based on Machine Learning. Issue 2 (June 2021) - Wen, Gege; Wen, Pin; Tang, Zukai
Abstract: This paper uses conditional random field model to mine TCM data. In order to identify the information of prescriptions in ancient Chinese medicine books, the model firstly cleaned and segmented the original text data, then, labels are added according to the selection of TCM characteristics to mark part of the corpus, and according to the demand divided into two parts, the training corpus was used to adjust the parameters of the custom CRF feature template, and the model was generated after adjusting the parameters. The accuracy of the model for entity recognition was verified by using the test corpus. In the end, the feasibility of the conditional random field model in the identification of TCM prescriptions was verified experimentally.